2018
DOI: 10.1002/isd2.12059
|View full text |Cite
|
Sign up to set email alerts
|

Application of information and communication technology for internationalization of Nigerian small‐ and medium‐sized enterprises

Abstract: Information and communication technology (ICT) has fundamentally transformed business transactions. While its uses have become ubiquitous in the advanced economies, emerging and developing economies are still struggling with the mode and manner of the deployment of ICT for business. Thus, this study seeks to investigate how small-and medium-sized enterprises (SMEs) utilize ICT in Nigeria for business internationalization. To achieve the goal of the study, a mixed-method was employed.A questionnaire was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 70 publications
(153 reference statements)
5
24
0
2
Order By: Relevance
“…This was further mentioned by other participants (A15, A22] and A23). This finding was consistent with previous studies (Gholami et al, 2009;Zafar and Mustafa, 2017;Rahayu and Day, 2017;Gbadegeshin et al, 2019).…”
Section: Technologysupporting
confidence: 94%
See 4 more Smart Citations
“…This was further mentioned by other participants (A15, A22] and A23). This finding was consistent with previous studies (Gholami et al, 2009;Zafar and Mustafa, 2017;Rahayu and Day, 2017;Gbadegeshin et al, 2019).…”
Section: Technologysupporting
confidence: 94%
“…"DMD helps to relate to our customers, without it it will be difficult to relate with customers and meet their desires [-]" M12. This is consistent with Moon (2003) that found that when technology plays an essential role in the buying decision process, their performance is critical to business success Chinedu-Eze, 2018a, 2018b;Gbadegeshin et al, 2019). The implication of this is that SME managers are willing to adopt DMD if it would help them acquire new ones and retain the existing ones.…”
Section: Environmentsupporting
confidence: 81%
See 3 more Smart Citations